Kültür Varlıklarını Koruma Kurullarının İşleyişleri; Hollanda ve Belarus Örnekleri ile Karşılaştırılması - Çelebi, Hüseyin (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
Bu çalışmada kültürel mirası koruma kavramının tarihsel gelişimi ve bu gelişmeye bağlı olarak korumaya yönelik faaliyetlerde tek yetkili kurum olan Koruma Bölge Kurullarının öncüleri olan kurum ve kuruluşların tarihsel gelişimleri araştırılarak, kültürel mirası koruma politikalarının zamanla uğradıkları değişimleri ve en son şekillerinin kültürel mirasın korunmasına olan etkisinin değerlendirilmesi amaçlanmaktadır. Osmanlı imparatorluğundan bugüne kadar kültürel mirası koruma faaliyetlerinin nasıl evirildiği, hangi kurumlar tarafından ele alındığı, mevcut mevzuat içinde önemli bir role sahip olan 2863 sayılı yasa ve alt mevzuat olan yönetmelik ve ilke kararı incelenerek mevzuat içinde Koruma Bölge Kurulu müdürlüklerine tanınan hak ve yetkiler açıklanmaya çalışılmıştır. Uluslararası yasal düzenlemeler incelenerek ülkemizde koruma çalışmalarını ne ölçüde etkilediği değerlendirildikten sonra örnek devletler olarak seçilen Hollanda ve Belarus’un kültürel mirasın korunmasındaki mevzuatı ile koruma sürecini yürüten kurumların ülkemizdeki kurum ve mevzuatla karşılaştırılarak öneriler getirilmiştir.

In this study, it is aimed to evaluate the historical development of the concept of cultural heritage protection, the historical development of the institutions and organizations that are the pioneers of the Conservation Regional Boards, which is the only authorized institution in the activities for protection, the changes that the cultural heritage protection policies have undergone over time and the effect of the latest forms on the protection of the cultural heritage. It has been tried to explain how the concept of protectionism developed from the Ottoman Empire to the present and which institutions dealt with the concept of protection. By examining the law no. 2863 and the sub-legislation regulation and policy decision in force within the legal framework, it has been tried to determine the rights and authorities granted by the legal framework to the protection board directorates. After examining the international legal regulations and evaluating the extent to which they affect the conservation efforts in our country, suggestions have been made by comparing the legislation of the Netherlands and Belarus, which were selected as sample states, on the protection of cultural heritage and the institutions that carry out the protection process with the institutions and legislation in our country.
The Functioning of Cultural Asset Committees for The Protection; Comparison with The Examples of The Netherlands and Belarus
Keywords: Kültürel Miras; Koruma Bölge Kurulları; 2863 Sayılı Yasa; Tescil; Cultural Heritage; The Law Numbered 2863; Registration